Factors Influencing Transcultural Self-Efficacy Among Nurses With Foreign Patient Care Experience. (January 2022) - Ham, HyunJung; Tak, Sunghee H.
Introduction: As the cultural diversity among patients increases, it becomes important for nurses to be prepared and efficient in providing culturally congruent care. The purpose of this study is to examine the factors influencing transcultural self-efficacy (TSE) among Korean nurses. Methodology: A descriptive cross-sectional survey was used, and 131 nurses with foreign patient–care experience were recruited from a university tertiary hospital Results: The mean TSE score of participants was 5.27 out of 10 ( SD = 1.50). The practical subscale of TSE was the lowest, while the affective subscale was the highest. A regression analysis revealed that education level, cultural competence, and intergroup anxiety are predictors explaining 58.8% of its variance ( F = 27.5, p < .001). Discussion: A low level of TSE causes avoidant behavior and ineffective communication in foreign patient care, resulting in unsatisfactory clinical performance. Effective education programs and administration guidelines may be critical for nurses to improve their TSE.